A global discussion about our possible futures during the 2021 World Future Day. (February 2022) - Di Berardo, Mara
Abstract: During the World Future Day on March 1, the Millennium Project (MP) organizes a 24-hour around-the-world conversation for futurists and the public joining at noon to discuss their views about challenges and opportunities for the futures of humanity for building a better future together. The short communication distills the main suggestions and solutions discussed during the 2021 WFD, setting a global agenda for further discussion. Highlights: Rights of Nature, regenerative practices, plant- and cell-based meat to reduce GHGs. Increasing merger of humanity and technology. Increasing intelligence, creativity and futures literacy as objectives of education. A UN Office to coordinate research on how to address threats to human survival. The World Future Day as a unique global participatory discussion about our futures.